2017
DOI: 10.1016/j.ceca.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1, Orai1, and STIM1 in SOCE: Friends in tight spaces

Abstract: Store-operated calcium entry (SOCE) is a ubiquitous Ca2+ entry pathway that is activated in response to depletion of ER-Ca2+ stores and critically controls the regulation of physiological functions in miscellaneous cell types. The transient receptor potential canonical 1 (TRPC1) is the first member of the TRPC channel subfamily to be identified as a molecular component of SOCE. While TRPC1 has been shown to contribute to SOCE and regulate various functions in many cells, none of the reported TRPC1-mediated cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 78 publications
4
144
0
Order By: Relevance
“…Thus, the contribution of TMEM16A to EGF-induced Ca 2+ signaling appears to be particular related to the engagement of TMEM16A with EGFR. SOCE is usually described by the aggregation of STIM1 into punctae following the depletion of intracellular Ca 2+ stores, and their association with ORAI proteins at the plasma membrane to form functional Ca 2+ channels that mediate Ca 2+ influx (29,30).…”
Section: Egf Induces a Transient Calcium Response And Activates Caccmentioning
confidence: 99%
“…Thus, the contribution of TMEM16A to EGF-induced Ca 2+ signaling appears to be particular related to the engagement of TMEM16A with EGFR. SOCE is usually described by the aggregation of STIM1 into punctae following the depletion of intracellular Ca 2+ stores, and their association with ORAI proteins at the plasma membrane to form functional Ca 2+ channels that mediate Ca 2+ influx (29,30).…”
Section: Egf Induces a Transient Calcium Response And Activates Caccmentioning
confidence: 99%
“…48 Although there exist arguments on whether TRPC1 is a component of SOCE channel, 49 our recent results from human cardiac c-Kit + progenitor cells 13 support the notion that TRPC1 works together with Orai1 to form discrete STIM1-gated SOCE channel, mediate distinct Ca 2+ signals and regulate specific cellular functions. [50][51][52] The present study shows that bradykinin-induced Ca 2+ In Ca 2+ signalling, very low cytoplasmic Ca 2+ concentration can increase in a specific manner to trigger downstream cellular events, and every cell type in the human body utilizes some form of Ca 2+ signalling to function or survive. 29 Ferreira-Martins and colleagues reported that spontaneous Ca 2+ oscillations promote human cardiac c-Kit + progenitor cell proliferation.…”
Section: Ca 2+ Signalling By Bradykinin and Intracellular Signal Momentioning
confidence: 65%
“…In particular, there has been debate about the role or opening mechanisms of TRPC1. Initially, TRPC1 was claimed to take the role of a SOCE in regulating Orai1-mediated Ca 2+ entry (Ambudkar et al, 2017). Consistent with this claim, the role of TRPC1 in AD has been reported by Linde et al (2011).…”
Section: Trpc1mentioning
confidence: 72%